Local injection of DFO on bone remodeling of alveolar bone: An experimental study in the mouse - ZHANG Qian; KANG Feiwu (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of local injection of desferrioxamine (DFO) on the bone remodeling of alveolar bone through the regulation of osteoclasts by hypoxia inducible factor-1α (HIF-1α). [Methods:] DFO was injected locally into the alveolar bone of C57 mice; changes in alveolar bone volume were observed by micro-CT and histological staining; osteoclastogenesis was observed by immunofluorescence and tartrate-resistant acid phosphase (TRAP) staining; the effects of DFO on the differentiation of Raw264.7 to osteoclasts via HIF-1α were observed in vitro by TRAP staining and immunofluorescence. [Results:] Micro-CT and histological staining showed that local bone density decreased and bone volume decreased after local injection of DFO; histological staining revealed that the number of local osteoclasts increased and HIF-1α expression increased in the DFO injection group compared with the control group; in vitro cell culture revealed that DFO promoted the expression of HIF-1α in Raw264.7 cells and its differentiation to osteoclasts. [Conclusion:] Local injection of DFO can promote bone remodeling of alveolar bone and differentiation of Raw264.7 into osteoclasts.